2015
DOI: 10.1186/s40478-015-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

Early neurone loss in Alzheimer’s disease: cortical or subcortical?

Abstract: Alzheimer’s disease (AD) is a degenerative disorder where the distribution of pathology throughout the brain is not random but follows a predictive pattern used for pathological staging. While the involvement of defined functional systems is fairly well established for more advanced stages, the initial sites of degeneration are still ill defined. The prevailing concept suggests an origin within the transentorhinal and entorhinal cortex (EC) from where pathology spreads to other areas. Still, this concept has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
158
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 105 publications
(122 reference statements)
8
158
1
Order By: Relevance
“…In sum, our findings build on a varied body of histological evidence, which collectively point to both Ch4 and EC as early targets of AD pathology8. The cell groups constituting these structures are among the first to express intraneuronal neurofibrilliary tangles and Aβ-containing plaques in cognitively normal older adults.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In sum, our findings build on a varied body of histological evidence, which collectively point to both Ch4 and EC as early targets of AD pathology8. The cell groups constituting these structures are among the first to express intraneuronal neurofibrilliary tangles and Aβ-containing plaques in cognitively normal older adults.…”
Section: Discussionsupporting
confidence: 63%
“…The cell groups constituting these structures are among the first to express intraneuronal neurofibrilliary tangles and Aβ-containing plaques in cognitively normal older adults. They are also among the cell groups most devastated by tangles and plaques in MCI and AD81114. The proliferation of tangles and plaques in these structures leads to depletion of axons and cell loss, both of which contribute to microstructural decreases in volume8151718.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, volume reduction of the BNM and temporal lobe structures was associated with impairment in delayed recall in MCI patients (Grothe et al, 2010). These findings are consistent with neuronal loss in the BNM during the prodromal stage of AD and greater neuronal loss in the BNM than other cortical and subcortical structures in advanced AD (Arendt et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
“…Downregulation of Drd2 and Adra1b may be related to dysfunction and neurodegeneration of catecholaminergic systems, including the ventral tegmental area and locus coeruleus (Bondareff et al, 1987; Gibb et al, 1989; Mann et al, 1980), during the progression of AD, which would cause dysregulation of inputs to the cholinergic nbM (Jones and Cuello, 1989; Smiley and Mesulam, 1999; Smiley et al, 1999; Zaborszky and Cullinan, 1996). In particular, we and others have shown that locus coeruleus noradrenergic neuron loss occurs very early in the disease process (Arendt et al, 1985, 2015; Kelly et al, 2017; Theofilas et al, 2017) and likely contributes to disruptions in cholinergic modulation of attentional function. Glutamate-mediated excitotoxicity has been implicated in AD neuronal dysfunction and cognitive impairment, and dysregulation of the Grin2B -encoded NMDA receptor 2B subunit appears to be a primary pathogenic event in disease progression (Andreoli et al, 2013; Hu et al, 2012; Olney et al, 1997).…”
Section: Discussionmentioning
confidence: 81%